The Influence of Government Size, Intergovernmental Transfers, Regional Expenditure, and Audit Findings on Local Government Financial Performance in Indonesia - Argianov Ramadhan; Sri Rahayu; Rico Wijaya Z (Darul Yasin Al Sys, 2026)
Local government financial performance is a key indicator for evaluating the success of regional autonomy and the effectiveness of public financial management. However, disparities in financial performance across Indonesian provinces reflect differences in fiscal capacity and the quality of regional financial governance. This study aims to analyze the effects of government size, intergovernmental transfers, regional expenditure, and audit findings on local government financial performance in Indonesia. A quantitative approach was employed using secondary data obtained from the Audit Reports of the Supreme Audit Board of the Republic of Indonesia for the 2022–2024 period. The sample comprised 34 provincial governments selected through purposive sampling, yielding 102 observations. Data were analyzed using panel data regression with EViews 13. The findings reveal that government size and regional expenditure have a significant negative effect on local government financial performance. In contrast, intergovernmental transfers have a significant positive effect, while audit findings have no significant effect. These results indicate that effective resource management and fiscal capacity play a more decisive role in strengthening financial performance than asset magnitude or the number of audit findings. This study contributes to public sector financial management literature by providing empirical evidence on the determinants of provincial financial performance in Indonesia. The practical implications emphasize the need to optimize asset management, utilize intergovernmental transfers effectively, and allocate regional expenditure toward more productive activities to improve financial performance and strengthen local fiscal independence.